Mathematical modeling of cancer metabolism - Medina-Torres, Miguel Ángel (My University, 2018)
Systemic approaches are needed and useful for the study of the very complex issue of cancer. Modeling has a central position in these systemic approaches. Metabolic reprogramming is nowadays acknowledged as an essential hallmark of cancer. Mathematical modeling could contribute to a better understanding of cancer metabolic reprogramming and to identify new potential ways of therapeutic intervention. Herein, I review several alternative approaches to metabolic modeling and their current and future impact in oncology.
Keywords: Cáncer - Metabolismo; Modeling; Cancer; Metabolism